An integrative review of social and occupational factors influencing health and wellbeing - Gallagher, MaryBeth; Muldoon, Orla T.; Pettigrew, Judith (Frontiers in Psychology, 2015)
Therapeutic approaches to health and wellbeing have traditionally assumed that meaningful activity or occupation contributes to health and quality of life. Within social psychology, everyday activities and practices that fill our lives are believed to be shaped by structural and systemic factors and in turn these practices can form the basis of social identities. In occupational therapy these everyday activities are called occupations. Occupations can be understood as a contextually bound synthesis of meaningful doing, being, belonging and becoming that influence health and wellbeing. We contend that an integrative review of occupational therapy and social psychology literature will enhance our ability to understand the relationship between social structures, identity and dimensions of occupation by elucidating how they inform one another, and how taken together they augment our understanding of health and wellbeing This review incorporates theoretical and empirical works purposively sampled from databases within EBSCO including CINAHL, psychINFO, psychArticles and Web of Science. Search terms included: occupation, therapy, social psychology, occupational science, health, wellbeing, identity, structures and combinations of these terms. In presenting this review, we argue that doing, being and belonging may act as an important link to widely acknowledged relationships between social factors and health and wellbeing, and that interventions targeting individual change may be problematic.